Distribution of Mercury in Rainbow Trout Tissues at Embryo-Larval and Juvenile Stages - Renáta Kenšová; Kamila Kružíková; Jan Havránek; Danka Haruštiaková; Zdeňka Svobodová (The Scientific World Journal)
The aims of the study were to determine total mercury concentrations in “rainbow trout Oncorhynchus mykiss (Walbaum)” at their embryo-larval and juvenile stages and to assess mercury concentration dynamics in individual tissues. Samples of rainbow trout were collected at two-month intervals over a period of 18 months (one stock production cycle) at the Velká Losenice trout farm. Feedstuff samples were collected at the same time and analyzed for mercury concentrations. Tissue mercury concentrations were determined in muscle, liver, and kidneys. Analyses were performed using the AMA 254 atomic absorption spectrophotometer. The lowest mercury concentration was found in 14-day-old embryos (hard roe), and the highest concentrations in muscle tissue, liver, and kidneys at the end of monitoring, that is, in rainbow trout aged 18 months. The amount of mercury in feedstuffs showed an increasing trend and ranged between 0.0126 and 0.0859 mgkg−1. A significant effect (P<0.001) of mercury intake on mercury concentrations in muscle tissue, liver, and kidneys was demonstrated. Muscle mercury concentrations in 18-month-old market-ready rainbow trout of 0.128 ± 0.048 mgkg−1 met the criteria for fish meat hygiene.